1987
DOI: 10.1139/b87-234
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of winter respiratory response to temperature, moisture, and freeze–thaw exposure in Bouteloua gracilis dominated grassland soils of southwestern Alberta

Abstract: 1987. The pattern of winter respiratory response to temperature, moisture, and freeze-thaw exposure in Bouteloua gracilis dominated grassland soils of southwestern Alberta. Can. J. Bot. 65: 1716-1725. Winter respiratory activity of soils from Bouteloua gracilis dominated grassland of southwestern Alberta was examined, both under in situ field conditions and over a matrix of defined laboratory conditions. The effect of winter thaw conditions was very pronounced on observed rates of soil surface CO, evolution. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…6). Studies of Coxson & Parkinson (1987) and Kähkönen et al . (2001) have shown that soil microbes can be active down from −7.5 to −5 °C.…”
Section: Resultssupporting
confidence: 85%
“…6). Studies of Coxson & Parkinson (1987) and Kähkönen et al . (2001) have shown that soil microbes can be active down from −7.5 to −5 °C.…”
Section: Resultssupporting
confidence: 85%
“…During winter, NEE was relatively steady and weakly positive. This observation is consistent with the following suggestions: (1) cold soil temperature (daily mean < 5 °C) may limit root water uptake as well as the stomatal conductance, and thus carbon uptake by the trees (DeLucia, 1986;Day et al, 1991;Sperry, 1993); (2) detectable microbial respiration existed in the soil even below the freezing point (e.g., Coxson and Parkinson, 1987). With the onset of snowmelt in April, NEE became more positive and variable, probably because increasing temperatures after snowmelt caused an increase in microbial respiration and root respiration.…”
Section: Net Ecosystem Co2 Exchangesupporting
confidence: 91%
“…6). Although cold temperatures limit biological processes (Conant et al, 2011;Nadelhoffer et al, 1991), microbes can remain active well below 0°C (Mikan et al, 2002;Miller et al, 2007), and can survive as long as liquid water films are present (Coxson and Parkinson, 1987); liquid water films have been observed down to −10°C (Romanovsky and Osterkamp, 2000). In the EML catchment, winters are characterized by deep snowpacks that insulate soils to near 0°C (Sickman et al, 2003a), allowing for the metabolism of senesced biomass deposited in the autumn and mineralization/immobilization of nutrients (Taylor and Jones, 1990).…”
Section: Soil P Retentionmentioning
confidence: 99%